A Study of Listening Difficulties among EFL Learners in the ‘Understanding Talk’ Course - Salsabila, Bilkis; Rayanto, Yudi Hari; Mabaroh, Baratun (Indonesian Journal of Multidisciplinary Educational Research, 2026)
This study examines linguistic and non-linguistic factors affecting students’ listening comprehension in the Understanding Talk course. Using a quantitative descriptive design, data were collected from 20 second-semester EFL students at Universitas PGRI Wiranegara through a 20-item Likert-scale questionnaire validated by expert judgment. Data were analyzed using mean scores and percentage distributions, with difficulty levels categorized into four scales. The findings reveal that key linguistic difficulties include limited vocabulary (M = 2.10), complex grammar (M = 2.05), fast speech rate (M = 2.25), and unfamiliar pronunciation (M = 2.30), all classified as high difficulty. Non-linguistic challenges such as background knowledge (M = 2.15), audio quality (M = 2.20), and cultural differences (M = 2.30) also play significant roles. These results suggest that listening difficulties arise from both linguistic and contextual factors. Pedagogically, integrated strategies involving vocabulary support, varied listening exposure, and improved audio quality are recommended.